Development and predation of Tupiocoris cucurbitaceus feeding on Tetranychus urticae - Cuello, Eliana Marina (2021)
We evaluated the predatory bug, Tupiocoris cucurbitaceus as biocontrol agent of the two spotted spider mite, Tetranychus urticae, by analysing its predatory capacity, development to adult stage when fed on this pest, and the effect of predation on T. urticae population. T. cucurbitaceus was capable of killing spider mites although failed to fully develop when fed on them. A negative effect on the development of spider mite population was registered when T. cucurbitaceus was present. However, its own population decreased during the evaluated period and small nymphs were not recorded. Our results show that T. cucurbitaceus cannot control T. urticae when this is the only pest present.